Pediatric Osteoarticular Infections Caused by Mycobacteria Tuberculosis Complex: A 26-Year Review of Cases in San Diego, CA. Issue 5 (30th December 2021) - Drobish, Ian; Ramchandar, Nanda; Raabe, Vanessa; Pong, Alice; Bradley, John; Cannavino, Christopher
Abstract : Background: Osteoarticular infections (OAIs) account for 10%–20% of extrapulmonary Mycobacteria tuberculosis (MTB) complex infections in children and 1%–2% of all pediatric tuberculosis infections. Treatment regimens and durations typically mirror recommendations for other types of extrapulmonary MTB, but there are significant variations in practice, with some experts suggesting a treatment course of 12 months or longer. Methods: We conducted a retrospective review of children diagnosed with MTB complex OAI and cared for between December 31, 1992, and December 31, 2018, at a tertiary care pediatric hospital near the United States–Mexico border. Results: We identified 21 children with MTB complex OAI during the study period. Concurrent pulmonary disease (9.5%), meningitis (9.5%), and intra-abdominal involvement (14.3%) were all observed. MTB complex was identified by culture from operative samples in 15/21 children (71.4%); 8/15 (53.3%) cultures were positive for Mycobacterium bovis. Open bone biopsy was the most common procedure for procurement of a tissue sample and had the highest culture yield. The median duration of antimicrobial therapy was 52 weeks (interquartile range, 46–58). Successful completion of therapy was documented in 15 children (71.4%). Nine children (42.9%) experienced long-term sequelae related to their infection. Conclusion: Among the 21 children with MTB complex OAI assessed, 8 of 15 (53.3%) children with a positive tissue culture had M. bovis, representing a higher percentage than in previous reports and potentially reflecting its presence in unpasteurized dairy products in the California-Baja region. Bone biopsy produced the highest culture yield in this study. Given the rarity of this disease, multicenter collaborative studies are needed to improve our understanding of the presentation and management of pediatric MTB complex OAI.